Examining the Impact of HRD Practices on Organizational Commitment and Intention to Stay Within Selected Software Companies in India. Issue 1 (February 2018) - Uraon, Ram Shankar
The Problem: Software companies are knowledge-based organizations, they invest considerably on human resource development (HRD) practices to overcome the shortage of competent workforce, to stay competitive in the dynamic and competitive business environment of today. Furthermore, software companies are continuously involved in HRD interventions for the development of employees; problems such as low levels of employee commitment, employee engagement, and employee intention to stay are the biggest challenges. The Solution: This study examined the impact of comprehensive HRD practices on organizational commitment (affective, continuance, and normative commitment), and employee intention to stay. In addition, it examined the impacts of organizational commitment on employee intention to stay. Survey responses were collected from 516 employees working in different software companies in India. Data were analyzed using partial least squares (PLS) method. Results showed that HRD practices have positive impacts on employee intention to stay as well as on the three components of organizational commitment. Furthermore, only affective and normative commitments were found to positively affect employees' intention to stay, whereas relationship between continuance commitment and intention to stay was found to be negative and not significant. The Stakeholders: Implications for software companies, HRD professionals, and scholars: First, software companies may like to formulate their strategies keeping organizational commitment and employee intention to stay in focus. Second, human resource (HR) managers are encouraged to develop a metric to assess the value added by each HRD practice in managing attrition. This study contributes to the existing concepts on links between HRD practices and attitudinal variables by suggesting a theoretical framework. Finally, it provides empirical evidence that HRD practices in software companies must be sound to enhance employee intention to stay and organizational commitment in India.